Transactions of Cryptocurrency in the Perspective of Islamic Finance and Economics - Batubara, Maryam; Tho’in, Muhammad (Muqtasid: Jurnal Ekonomi dan Perbankan Syariah, 2023)
Cryptocurrency is a growing fintech trend frequently encountered in various moderneconomic activities. Therefore, this research aimed to provide knowledge and understanding of cryptocurrency, particularly from the perspective of Islamic finance and economics using secondary data obtained from literature. As a digital financial transaction system, cryptocurrency fundamentally uses relatively new technology. However, the legal nature still needs further examination without constituting a form of violation. In Indonesia, the government has yet to adopt a definitive stance on the presence of cryptocurrency, thereby permitting its usage. The results showed that cryptocurrency investment includes substantially greater risk compared to others due to the inherent challenge of predicting the value. From the perspective of Islamic finance and economics, the transactions are considered to lack clarity in terms of quality and quantity, containing elements of uncertainty (gharar). Moreover, the concept of Bitcoin as a transaction tool is forbidden (haram) by the Indonesian Ulama Council since the project contains uncertainty and does not comply with the existing regulations. The implications of the research emphasize the necessity ofavoiding dubious activities, such as cryptocurrency, as well as transactions leading to higher harm (madharat) compared to benefits, particularly from the perspective of Islamic finance and economics.